Ripped from the pages eaudiobook - Carlisle, Kate (Bibliophile Mystery, 2015)
Excited to explore the secrets of wine country, Brooklyn attends an excavation of the caves hidden deep under her parents' commune - and the findings are explosive. A room is unearthed, and it contains a treasure trove of artwork, rare books, a chest of jewelry...and a perfectly mummified body. A closer examination of the murdered man's possessions reveals a valuable first edition of Jules Verne's A Journey to the Center of the Earth. Hidden in the book is a secret map that unveils an even greater hoard of treasures. As reporters and art appraisers flock to Sonoma to see the precious bounty, questions begin to rise. But not all crime is buried in the past. When a new presence threatens the town's peace, Brooklyn decides to do a little excavating of her own...